Shigatoxigenic Escherichia coli contamination in chicken meat stalls in a district of Lima, Peru - Lucas L., Juan Raúl (2016)
The aim of this study was to determine if chicken meat stalls are sources of contamination with shigatoxigenic Escherichia coli (STEC) in Lima, Peru. Swabs from the surfaces of hands, cutting boards and sale tables of 50 chicken meat stalls in a large market in the district of San Juan de Miraflores, Lima, Peru were taken (n=150 samples). Standard microbiological isolation and molecular identification of stx1, stx2 and eaeA genes by PCR was performed. Results showed that 42% (63/150) and 25.3% (38/150) of samples were positive for E. coli and STEC respectively. Besides, 84% (42/50) and 66% (33/50) of chicken meat stalls had at least one contaminated surface with E. coli and STEC respectively. Also, 68.3% (43/63) of strains of E. coli isolated were pathogenic for presenting at least one of the evaluated genes. There were 38 STEC strains and presented stx1 (19.0%, 12/63), stx2 (14.3%, 9/63) and the associations stx1 and stx2 (12.7%, 8/63), stx1, stx2 and eaeA (6.3%, 4/63), stx2 and eaeA (4.8%, 3/63), and stx1 y eaeA (3.2%, 2/63). Poor hygiene practices were observed in the chicken meat retail stores. It is confirmed that chicken meat stalls in the Lima market were potential sources of contamination of STEC.